Epstein–Barr virus encoded microRNAs target SUMO‐regulated cellular functions. (30th September 2014) - Callegari, Simone; Gastaldello, Stefano; Faridani, Omid R.; Masucci, Maria G.
<x xml:space="preserve">Abstract</x> Post‐translational modification by the small ubiquitin‐like modifier (SUMO) regulates the cellular response to different types of stress and plays a pivotal role in the control of oncogenic viral infections. Here we investigated the capacity of microRNAs (miRNAs) encoded by Epstein–Barr virus to interfere with the SUMO signaling network. Using a computational strategy that scores different properties of miRNA–mRNA target pairs, we identified a minimal set of 575 members of the SUMO interactome that may be targeted by one or more Epstein–Barr virus miRNAs. A significant proportion of the candidates cluster in a functional network that controls chromatin organization, stress, DNA damage and immune responses, apoptosis and transforming growth factor beta signaling. Multiple components of the transforming growth factor beta signaling pathway were inhibited upon upregulation of the BamHI‐H rightward open reading frame 1 (BHRF1) encoded miRNAs in cells transduced with recombinant lentiviruses or entering the productive virus cycle. These findings point to the capacity of viral miRNAs to interfere with SUMO‐regulated cellular functions that control key aspects of viral replication and pathogenesis.